Robust Control and Co-simulation of a Multivariable Nonlinear Liquid Level Control System - Bueno, Átila M. [UNESP]; Serni, Paulo J. A. [UNESP]; Machado, Rodolfo G. [UNESP]; Dermendjian, Fábio H. [UNESP]; Balthazar, José M. [UNESP] (Springer Nature, 2022)
Introduction: Co-simulation is a technique to overcome difficulties related to the simulation of a system running in multiple environments. It is accomplished performing the global simulation by composing different simulation machines. Purpose: In this work, the development of a co-simulation system for a multivariable Tthree-Ttank liquid level system is presented. Method: The simulation of the Three-Tank liquid level system runs part in a digital computer, in the LabViewTM system, and part in an analogue computer in order to feature both discrete and analogue models connected by a data communication system. The robust controller designed with the LQG/LTR technique is implemented using SciLabTM application. Additionally, an alternative setup is considered, implementing the previous analogue computer in a circuit simulator, the Electronics Workbench EWBTM. The data communication between the plant and the controller (process variables and control signals) is developed using the Open Platform Communications (OPC) industrial communications protocol. Conclusion : The proposed co-simulation technique is suitable to integrate different simulation software and machines with pre-existent facilities or structures and new developments, even if remotely located, and allowing to assess the performance of control systems, sensors, actuators, and embedded software and hardware.
Keywords: Co-simulation; LQG/LTR controller; Multivariable control; Nonlinear control; Open platform communications (OPC)